The transformative impact of financial technology on behavioral finance - Lemishko, O. (Економічний вісник Донбасу, 2024)
The article defines behavioral finance as a subject area of science that includes examination, systematization, and further implementation of behavioral tools in the functioning of finance at the macro and micro levels in order to substantiate the cause-and-effect relationships between the behavioral orientation of the financial relations subject regarding financial decision-making and objective economic reality. The relationship between financial technologies and the behavior of participants in financial relations is analyzed. It is shown that the transformative impact of financial technologies lies in changing the focus to the rationality of the subject's choice and in accelerating the making of financial decisions. Stated above is a guarantee of ensuring innovation in all aspects of the global financial landscape. For financial technologies to have a positive impact on behavioral finance, it is necessary to create a favorable regulatory environment which is adapted to modern legislative requirements, balanced legislative regulation, and protection of the rights of clients using financial technologies. В статті означено біхевіористичні фінанси, як предметну область науки, що включає опрацювання, систематизацію і подальшу імплементацію поведінкового інструментарію у функціонування фінансів на макро- і мікрорівнях з метою обґрунтування причинно-наслідкових зав’язків між поведінковою орієнтацією суб’єкта фінансових відносин щодо прийняття фінансових рішень і об’єктивною економічною реальністю. Проаналізовано взаємозв’язок фінансових технологій і поведінки учасників фінансових відносин. Показано, що трансформуючий вплив фінансових технологій полягає у зміні фокусу на раціональність вибору суб’єкта, у прискоренні прийняття фінансового рішення. Означене є запорукою забезпечення інноваційності у всіх аспектах глобального фінансового ландшафту. Визначено, що для позитивного впливу фінансових технологій на біхевіористичні фінанси необхідно сформувати сприятливу регуляторну середу, адаптовану сучасним законодавчим вимогам, захисту прав клієнтів, що використовують фінансові технології.